Prevalence and Correlates of HIV Disclosure Among Children and Adolescents in Low- and Middle-Income Countries: A Systematic Review. Issue 6 (July 2016) - Britto, Carl; Mehta, Kayur; Thomas, Rwituja; Shet, Anita
ABSTRACT: Objective: Disclosure of HIV status among children and adolescents living with HIV has both beneficial and challenging aspects. To address existing knowledge gaps and update the literature on childhood disclosure, we conducted a systematic review on caregivers' perceptions and practices of HIV disclosure in low- and middle-income countries (LMICs). Methods: Standard databases were searched for studies conducted in LMICs, published in English between 2004 and 2015. Excluded articles were reviews or case reports, and those not reporting childhood disclosure. Data regarding prevalence, correlates and impact of disclosure, were presented as frequencies. Results: Two authors independently screened 982 articles. After applying eligibility criteria, 22 articles representing 12 countries and 2, 843 children were reviewed. The proportion of fully disclosed children ranged from 1.7% to 41.0%. Up to 49.5% children were provided "deflected" information (use of a non-HIV-related reason for explaining illness and health care visits). Factors associated with full disclosure included antiretroviral treatment initiation and caregivers' felt need for maintaining optimal adherence. Barriers to disclosure included fear of negative psychological reactions and inadvertent disclosure to others. Caregivers perceived a strong need for active participation from health care providers to aid the process of disclosure. Conclusions: Full disclosure of HIV status was not common among children and adolescents in LMICs, while the practice of deflected disclosure was prominent. Caregivers perceived the need for support from health care providers during the disclosure process. Evidence-based guidelines incorporating the developmental status of the child, locally prevalent cultures, and caregiver perceptions are prerequisite to enhancing disclosure in these settings.